Witchcraft continued: Popular magic in modern Europe - Davies, Owen (Manchester University Press, 2004)
Witchcraft continued provides an important collection of essays on the nature and understanding of witchcraft and magic in European society over the last two centuries. It innovatively brings together the interests of historians in nineteenth-century witchcraft and the twentieth-century fieldwork of anthropologists and sociologists on the continued relevance of witch beliefs. The book covers England, the Netherlands, Spain, Italy, Germany, France, Finland, Transylvania and Northern Ireland. It examines the experience of and attitudes towards witchcraft from both above and below. They demonstrate the widespread fear of witches amongst the masses during the nineteenth century, and the continued but more restricted relevance of witchcraft in the twentieth century. While the educated classes generally denounced witch-believers as either superstitious, foolish or both, secular and religious authorities still had to find strategies of dealing with the demands of those who believed themselves the victims of witchcraft. Moreover the rise of the folklore movement and the growth of anthropology as an academic discipline over the period provided a huge body of evidence on continuing beliefs that many had consigned to the past. This book will be essential reading for those interested in the continued importance of witchcraft and magic in the modern era. More generally it will appeal to those with a lively interest in the cultural history of the nineteenth and twentieth centuries.